The impacts of cultural policy on gaming entrepreneurs in Shanghai: an entrepreneurial ecosystem approach. Issue 4 (8th August 2022) - Huang, Gejun
ABSTRACT: China's cultural policy has been a key driver to the formation and development of the domestic digital game industry. In line with the nationwide promotion of "Mass Entrepreneurship and Innovation" since 2015 (He et al., 2019), there has witnessed an increasing emphasis on entrepreneurship in the related cultural policies at the local level, especially in China's major cities known for high-tech creative clusters. Focusing on the thriving gaming entrepreneurship in Shanghai, this article adopts an entrepreneurial ecosystem approach to examine the under-studied relationship between the creation of gaming ventures and the relevant set of cultural policy. Drawing on 33 gaming entrepreneur interviews complemented by policy content, this article provides rich accounts of how gaming entrepreneurs react to and reflect on the local cultural policy in relation to two key elements of the entrepreneurial ecosystem: financial capital availability and support services. The findings shed new light on creative autonomy and cultural policy in China.